PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Mutiara Noor Febriani (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2022)
The purpose of this observe was become identify and analyze the impact of servicequality and promotion on purchasing decisions in Kopi Pasir Aladdin Tasikmalaya. Theresearch method used is a survey method, while the population in this study are all consumers in Kopi Pasir Aladdin Tasikmalaya who have made a purchase. Data obtained directly with field information on 100 consumers and the method used in this study is multiple linear regression analysis. The results of this study indicate that Service Quality and Promotion simultaneously have a significant effect on Purchase Decisions at Kopi Pasir Aladdin Tasikmalaya. The results of this study indicate that Service Quality partially has a significant effect on Purchase Decisions at Kopi Pasir Aladdin Tasikmalaya, Promotion partially has a significant effect on Purchase Decisions at Kopi Pasir Aladdin Tasikmalaya